Strategies for Increasing Teacher Competence through Structured Mentoring in Developing Local Wisdom-Based Curriculum in Az-Zahwa Playgroup - Putri Rahayu, Dika (Al-Athfal: Jurnal Pendidikan Anak, 2020)
The curriculum is an absolute thing that must be owned by a teaching unit. The curriculum is the core of the learning process. Az-Zahwa Playgroup Trenggalek has five teachers with high-school educational background and has never received training or workshops. This condition has an impact on the course during the learning process. The learning process runs without a plan, and the activities taken during the learning process was not appropriate to the children's age. This research aims to describe the strategies in increasing teacher competence, especially in pedagogic and professionalism based on structured-mentoring. In this research, the structured-mentoring was conducted by providing alternately structured materials and practice using prepared learning-tools appropriate to curriculum 2013. This type of research was qualitative with a case-study design. The data were collected using observations, interviews, and documentation. This research's inhibiting factor was that the teachers have a high-school educational background and have not had teaching experience, resulting in a lack of knowledge and teaching skills. On the other hand, the supporting factor was that teachers were enthusiastic and creative in developing the learning tools based on local culture. The results achieved from this structured-monitoring research were the teachers were able to make the learning-tools start from PROTA, PROMES, RPPM, RPPH according to 2013 Curriculum based on local culture and ended by generating the score by using work-result oriented techniques, checklist, portfolio, and anecdotal notes.